Single-gene speciation: mating and gene flow between mirror-image snails - Richards, Paul M.; Morii, Yuta; Kimura, Kazuki; Hirano, Takahiro; Chiba, Satoshi; Davison, Angus (Wiley, 2017)
Variation in the shell coiling, or chirality, of land snails provides an opportunity to investigate the potential for “single-gene” speciation, because mating between individuals of opposite chirality is believed not possible if the snails mate in a face-to-face position. However, the evidence in support of single-gene speciation is sparse, mostly based upon single-gene mitochondrial studies and patterns of chiral variation between species. Previously, we used a theoretical model to show that as the chiral phenotype of offspring is determined by the maternal genotype, occasional chiral reversals may take place and enable gene flow between mirror image morphs, preventing speciation. Here, we show empirically that there is recent or ongoing gene flow between the different chiral types of Japanese Euhadra species. We also report evidence of mating between mirror-image morphs, directly showing the potential for gene flow. Thus, theoretical models are suggestive of gene flow between oppositely coiled snails, and our empirical study shows that they can mate and that there is gene flow in Euhadra. More than a single gene is required before chiral variation in shell coiling can be considered to have created a new species.